2009
DOI: 10.1117/12.830683
|View full text |Cite
|
Sign up to set email alerts
|

193 nm angle-resolved scatterfield microscope for semiconductor metrology

Abstract: An angle-resolved scatterfield microscope (ARSM) featuring 193 nm excimer laser light was developed for measuring critical dimension (CD) and overlay of nanoscale targets as used in semiconductor metrology. The microscope is designed to have a wide and telecentric conjugate back focal plane (CBFP) and a scan module for resolving Köhler illumination in the sample plane. Angular scanning of the sample plane was achieved by linearly scanning an aperture across the 12 mm diameter CBFP, with aperture size as small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Theoretically, the scattering cross-section (SCS) of the defect is approximately proportional to d 6 /λ 4 , thus the scattering signal of the defects decreases with the shrinkage of defect size. Meanwhile, the scattering angles of the high diffraction orders from the background pattern will enlarge as the CD size shrinks [54]. Therefore, the SNR of the defect scattering signal will decrease with the shrinkage of defect size.…”
Section: Effect Of Topography On Defect Detectabilitymentioning
confidence: 99%
“…Theoretically, the scattering cross-section (SCS) of the defect is approximately proportional to d 6 /λ 4 , thus the scattering signal of the defects decreases with the shrinkage of defect size. Meanwhile, the scattering angles of the high diffraction orders from the background pattern will enlarge as the CD size shrinks [54]. Therefore, the SNR of the defect scattering signal will decrease with the shrinkage of defect size.…”
Section: Effect Of Topography On Defect Detectabilitymentioning
confidence: 99%
“…Previously, direct comparison between the imperfectly patterned die and another well-pattered die was hampered by substantially different illumination conditions. In this experiment, "Bx" and " By" defects are measured on two dies on the 9 nm IDA using bright-field illumination using the NIST 193 nm Microscope [11]. The full-field effective illumination numerical aperture (NA) is annular due to a catadioptric objective and ranges from 0.12 NA to 0.74 NA.…”
Section: Comparison Of Dies On the Sematech 9 Nm Idamentioning
confidence: 99%
“…Recent studies by our group have shown increases sensitivity to CD by tailoring the partial coherence factor and aperture shape in the CBFP (31). Quadrupole and dipole illumination have also been explored for enhancing the optical response from pattered ECS Transactions, 92 (1) 73-84 (2019) samples (32,33). Second, instead of an annulus or slit, a single finite aperture can be used to produce a narrow cone of light at the sample (25).…”
Section: Scatterfield Microscopymentioning
confidence: 99%